2016
DOI: 10.1016/j.jfma.2015.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of BRAF and NRAS mutations in cutaneous melanoma patients in Taiwan

Abstract: As BRAF and NRAS mutations are rare in Taiwan, BRAF- or NRAS-targeted therapies may be effective only for selected Taiwanese melanoma patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
29
4
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 21 publications
6
29
4
2
Order By: Relevance
“…However, BRAF and NRAS mutation frequencies are substantially lower in Asian melanoma patients. A recent study conducted in Taiwanese melanoma patients found that only 14.3% had BRAF mutations (of which 88.2% were BRAF V600E), and just 10.1% had NRAS mutations; moreover, patients with BRAF mutations were more likely to have thin melanomas and less ulceration, which differs from the prevailing phenotype usually observed in Asian patients . Among Chinese melanoma patients, the frequency of BRAF and NRAS mutations was found to be 25.5% and 7.2%, respectively .…”
mentioning
confidence: 95%
“…However, BRAF and NRAS mutation frequencies are substantially lower in Asian melanoma patients. A recent study conducted in Taiwanese melanoma patients found that only 14.3% had BRAF mutations (of which 88.2% were BRAF V600E), and just 10.1% had NRAS mutations; moreover, patients with BRAF mutations were more likely to have thin melanomas and less ulceration, which differs from the prevailing phenotype usually observed in Asian patients . Among Chinese melanoma patients, the frequency of BRAF and NRAS mutations was found to be 25.5% and 7.2%, respectively .…”
mentioning
confidence: 95%
“…Mutations in the pathway RAS/RAF/MEK/ERK of mitogen-activated protein kinase (MAPK) occur in almost 75% of cases of melanomas [1,2]. BRAF and NRAS are special targets for modern pharmacology and their activating mutations occur in 60-80% and 15-30% of melanomas, respectively [1,2,10]. In a meta-analysis of 36 studies of different melanoma subtypes, BRAF mutation was typical for SSMs (superficial spreading melanoma) and in those tumors arising on non-chronic ną na leczenie DTIC stwierdzono jedynie u 15-20% pacjentów [1,2,6,7].…”
Section: Molecular Targeted Treatmentmentioning
confidence: 99%
“…BRAF i NRAS są szczególnymi celami terapeutycznymi we współczes-Dermatology Review/Przegląd Dermatologiczny 2017/4 sun-damaged skin. By contrast, NRAS mutation is more prevalent in nodular melanomas (NM) and those arising on non-chronic sun-damaged lesions [10]. The most common V600E modification is responsible for 74-90% of BRAF mutations and it is caused by replacement of valine by glutamine acid.…”
Section: Leczenie Ukierunkowane Molekularniementioning
confidence: 99%
See 2 more Smart Citations